Pioneering the human development revolution - Haq, Khadija (New Delhi; Oxford University Press, 2008)
Contributed articles on Mahbub ul Haq, 1934-1998, Pakistani economist
Includes Reference
Keywords: Biographies; Cross-cultural studies; Economic development Developing countries Planning; Economists Pakistan Biography